Gamification Analysis in Ui And Ux for Parking Spot Apps - Emmanuel Himawan Saptaputra; Arsa Widitiarsa Utoyo; Nia Karlna (Bina Nusantara University, 2020)
Advances in personal computing and information technology have been updated and published online or via mobile devices. Consequently, we must consider interaction as a fundamental complement of representation in cartography and visualization. The user interface (UI) / UX (user experience) describes a series of concepts, guidelines and workflows to critically reflect on the design and use of an interactive, map- based or other product. This entry presents the basic concepts of UI / UX design that is important for cartography and visualization, focusing on issues related to visual design. First, a fundamental distinction is made between the use of an interface as a tool and the broader experience of an interaction, a distinction that separates UI design and UX design. The phases of the Norman interaction framework are not a different form of interaction structure. Finally, three dimensions of the user interface design are described: the fundamental interaction operators that form the basic blocks of the interfaces, the interface styles that these primitive operators implement and the recommendations for the visual design of an interface.